2017
DOI: 10.3168/jds.2016-11766
|View full text |Cite
|
Sign up to set email alerts
|

Can by-products replace conventional ingredients in concentrate of dairy goat diet?

Abstract: Intensive dairy goat production in the Mediterranean basin is based on imported conventional ingredients to be included in concentrates. Fourteen Murciano-Granadina goats in the middle of the third lactation were allocated into 2 groups of 7 animals each fed, respectively, a control diet based on alfalfa hay and concentrate in a 40:60 ratio, and a diet in which the concentrate included tomato fruits, citrus pulp, brewer's grain and brewer's yeast (T100CBY) to study the effect of diet on nutrient utilization, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 55 publications
(74 reference statements)
5
32
1
1
Order By: Relevance
“…De la Moneda et al [19] concluded that none of the seven different seaweed species, including Porphyra sp., tested in vitro for enteric CH 4 emission, had a noticeable anti-methanogenic effect. We measured values of enteric CH 4 from sheep fed the diets in respiration chambers between 22.8-29.1 L/kg DM intake, which is in accordance with observations made in goats [16,38], sheep [39] and cattle [40]. The in vivo results supported the results of the in vitro study, which also showed no significant differences in CH 4 emission between diets.…”
Section: In Vivosupporting
confidence: 88%
See 1 more Smart Citation
“…De la Moneda et al [19] concluded that none of the seven different seaweed species, including Porphyra sp., tested in vitro for enteric CH 4 emission, had a noticeable anti-methanogenic effect. We measured values of enteric CH 4 from sheep fed the diets in respiration chambers between 22.8-29.1 L/kg DM intake, which is in accordance with observations made in goats [16,38], sheep [39] and cattle [40]. The in vivo results supported the results of the in vitro study, which also showed no significant differences in CH 4 emission between diets.…”
Section: In Vivosupporting
confidence: 88%
“…Methane is an important greenhouse gas and represents an energy loss from the animal that results in reduced productivity. Because methane emissions are influenced by type of feed, ruminant nutritionists have focused studies on dietary strategies that can reduce CH 4 emissions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…When considering tomatoes as substitute of other ingredients in animal feed, such as in the diet of dairy goat, it implies a reduction in the methane production keeping the same milk yield (Molina-Alcaide et al, 2017). In an internalization of environmental cost, the role of environmental emissions in managing residues will be also included in the decision-making.…”
Section: Process Optimizationmentioning
confidence: 99%
“…The use of olive by-products in animal feed is growing and the evidence is positive, as the previous section has illustrated [33]. Nevertheless, such uses are still limited in comparison to low-value uses (energy and compost).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 94%